High Prevalence of Poststroke Depression in Ischemic Stroke Patients in Ethiopia - Fikru Tsehayneh; Abenet Tafesse (Neurology Research International)
Background. There is limited information and research carried out regarding the prevalence of poststroke depression (PSD) in the study area. Psychiatric disorders complicate a significant proportion of patients suffering from stroke. This of course have a great negative impact on our knowledge about poststroke depression in Ethiopia, and poststroke depression complicates a significant number of stroke patients and their rehabilitation. Methods. A cross-sectional study on all patients aged above 18 years and diagnosed with stroke in the past two years who attended the neurology follow-up clinics of Tikur Anbessa Specialized Hospital (TASH) and Zewditu Memorial Hospital (ZMH) was done by using a structured questionnaire containing Patient Health Questionnaire-9 (PHQ-9) depression screening tool. Result. Of 84 patients who were eligible for the study, 32.2% of patients have depressive symptoms. Women (OR 0.001, 95% CI 0.12–0.87) and aphasic patients (OR 0.034, 95% CI 0.19–1.27) were more likely to have depressive symptoms. Conclusion. Depressive symptoms after stroke are common in Ethiopian patients. Our study demonstrates female and aphasic patients are more likely to screen positive for PSD. Hence, screening all poststroke patients with different screening tools is practical, and further studies are needed to assess the validity of these screening tools and also to assess PSD as a predictor of stroke outcome.